NUCLEIC ACID SEQUENCE BASED AMPLIFICATION (NASBA)- PROSPECTS AND APPLICATIONS: Life Science-Microbiology - MD. FAKRUDDIN; MOHAMMAD MAZUMDAR, REAZ; CHOWDHURY, ABHIJIT; SHAHNEWAJ BIN MANNAN, KHANJADA (International Journal of Life Science and Pharma Research, 2012)
Nucleic acid sequence-based amplification (NASBA) is a sensitive, isothermal, transcription-based amplification system specifically designed for the detection of RNA targets. In some NASBA systems, DNA can also be amplified. This amplification system uses a battery of three enzymes (avian myeloblastosis virus reverse transcriptase, RNase H and T7 RNA polymerase) leading to main amplification product of singlestranded RNA. Expensive equipments are not necessary to acquire a high level of precision. NASBA is an established diagnostic tool in clinical use, with a theoretically bigger analytical sensitivity than reverse transcription-polymerase chain reaction (RT-PCR) for pathogen detection. It has a potential for detection of viable cells through selective amplification of messenger RNA, even in a background of genomic DNA, which PCR does not possess. In the future, NASBA could be used to identify and subsequently quantify microorganisms (even those which cannot be readily cultured) and would be very efficient as routine diagnostic procedures.